Seismic performance of high ductile RC frame designed in accordance with Malaysia National Annex to Eurocode 8 - Wong, Woon Keong (2020)
A few decades dated back, Malaysia was deemed as an earthquake free zone. However, this perception was changed after the 2004 Indian Ocean Earthquake and Tsunami incident which happened in Sumatra Indonesia, as well as the 2015 Ranau Earthquake. The introduction of Malaysia Seismic National Annex to Eurocode 8 in 2017 has triggered awareness in the construction industry in Malaysia. The national seismic annex suggests that only for building with Important Class IV shall be checked with inter-storey drift limit with the return period of 475 years. Thus, an investigation on the need of drift limit checks onto the buildings in Class I to III shall be checked for the inter-storey drift. This is because most of the seismic pre-code buildings are designed and detailed without ductile detailing. Furthermore, those buildings have a soft-storey feature with open space ground floor. Such building type is highly vulnerable to seismic attack, causing significant inter-storey drift. Therefore, there is a need to investigate the failure mode and plastic hinge formation in the ground soft-story RC buildings designed in accordance with the Malaysian National Annex to Eurocode 8. Non-linear pushover analysis onto typical 4-, 7- and 10-storey buildings frame are carried out in this study, using ETABS software. The aforementioned buildings are modelled in 3D, and to be designed and detailed as a high ductile reinforced concrete frame. The soft-story feature is also considered in this study. The results reveal that the high ductile RC building, which is the 4-storey building (all cases) and 7-storeys building (only ground type D cases) cannot achieve life safety requirement as per ASCE 41 (2007). The formation of CP plastic hinges occurred before the target displacement and targets base shear. For the other cases (7-storeys building with ground type B and all 10-storeys building case) fulfil the life safety requirements) Larger size of structural members is required in building with drift-controlled compare with the building without drift-controlled. Subsequently, the drift-controlled building is stiffer than the building without drift-control. As a result, the buildings have shorter target displacement and larger target base shear.